Komunikasi Whatsapp Group Dalam Meningkatkan Karakter Siswa Di Madrasah Ibtidaiyah - Faisal Faliyandra; Bagus Cahyanto; Yulina Fadilah; Muhammad Jadid Khadavi; Julia Setiowati (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
In the education process, teacher communication is not only with students, but communication with parents of students is very much needed. So in this study, communication innovation WhatsApp between teachers and parents becomes a special topic that will be discussed to improve the character of student. Then what is no less important is the ability of parents to interact with children in the process of forming children's character as a liaison for teachers at school. An experimental study using 2x2 ANOVA analysis was used in five elementary schools, with a sample of 102 students. The results of the study show that 1) information and communication technology such as WhatsApp Group can be an effective connecting tool to facilitate communication between teachers and parents to work together in shaping student character. 2) The emotional ability of parents to communicate is very effective for the formation of children's character. 3-4) High and low Islamic emotional abilities of parents are very effective in shaping the character of children at home. So the innovation of using social media to facilitate communication between teachers, parents, and students should not be ignored.